OPTIMISASI MULTI-OBJEKTIF PADA KINETIKA PENGERINGAN KABINET SURYA - Dzaky, Muhammad Irfan; Fauzi, Muhammad Burhanuddin (MACHINERY Jurnal Teknologi Terapan, 2022)
Drying is one method to increase the storage time of organic materials such as fruit, seeds and vegetables. The cheapest drying method that can be used is to use heat from the sun. The research carried out is to optimize the existing drying system using Design Expert software and MATLAB using the Multiobjective optimization genetic algorithm (MOGA) method. Based on the optimization that has been done, it can be concluded that the optimization results related to drying variables are flow rate, heat applied, drying load, and thickness which are seen based on the results of the minimum drying kinetics value and the minimum drying time on DE-MOGA, TOPSIS drying value. time (f1) is 35613.9 seconds and drying constant (f2) is 6,125 x 10-5 1/second with parameter flow rate (x1) is 0,037178 kg/second, heat input (x2) is 640,036 W/m2, loading density (x3) is 1.418 kg/m2, and thickness (x4) is 0.00662 m. The results of this optimization are very important to obtain optimal drying production results and the existing data can be used for design on other materials.